Odontogenic myxoma: Case report (Revista Nacional de Odontología, 2017)
Introduction: The objective was to determine a conservative or radical surgical treatment suitable for the odontogenic myxoma. Method: The study considered a clinical case of odontogenic myxoma in the upper jaw in an adult female patient, for which a radical treatment was chosen due to the size of the tumor. Results: The clinical case was assessed based on clinical, imaging, and histopathological criteria and according to the current scientific evidence. The en bloc resection treatment was determined for this case. Conclusions: Radical treatment, such as en bloc resection, seems to be the most appropriate to prevent recurrence of the tumor, especially in cases of extensive lesions such as the one reported.
Keywords: maxillary bones; jaw; myxoma; odontogenic tumors